IMPLEMENTASI KEGIATAN MAULID AL-HABSYI DI PONDOK PESANTREN WARATSATUL FUQAHA BANJARBARU - Afnanda, Mihrab; Farhah Mardhotillah Al Habsyi (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2025)
So far, the introduction of noble morals has been limited only through classroom learning, but in reality this is less effective in fostering noble morals. In an effort to deal with this, there needs to be a religious approach to Maulid Al-Habsyi activities. The objectives of this research are (1) to determine the implementation of Maulid Al-Habsyi at the Waratsatul Fuqaha Islamic Boarding School, Banjarbaru. (2) to find out the implications of Al-Habsyi's birthday at the Waratsatul Fuqaha Banjarbaru Islamic Boarding School. This research is qualitative research, which aims to find out the specifics and reality of what is happening at the moment. The results of this research show that (1) The implementation of Maulid Al-Habsyi has been carried out well because this activity is always routinely carried out every Wednesday night after the Maghrib prayer. (a) from the preparations for the Maulid Al-Habsyi activities, the students helped each other. (b) the implementation of cultivating noble morals towards Allah SWT, namely worshiping Allah SWT, noble morals towards Rasulullah Saw, namely reciting shalawat and greetings to Rasulullah Saw and imitating the morals of Rasulullah Saw by behaving according to the content of the poetry. (2) The implications of Maulid Al-Habsyi fostering noble morals for the students at the Waratsatul Fuqaha Islamic Boarding School, Banjarbaru, namely (a) noble morals towards Allah SWT. (b) noble morals towards Rasulullah SAW., (c) noble morals towards fellow human beings, namely, teachers, fellow friends and oneself.